A water retention model accounting for the hysteresis induced by hydraulic and mechanical wetting-drying cycles. (July 2017) - Azizi, Arash; Jommi, Cristina; Musso, Guido
Abstract: A comprehensive description of the water retention behaviour of unsaturated soils requires accounting for the hysteresis caused by hydraulic and mechanical wetting-drying cycles. A hysteretic water retention model is proposed by introducing the liquid-solid contact angle to account for the dependency of the response on non-monotonic changes in suction and void ratio. The proposed model reproduces main drying and wetting surfaces and also nonlinear scanning curves during hydraulic or mechanical loading. Experimental tests and numerical simulations were carried out to study the water retention behaviour of a clayey silt. The model simulations captured the experimental results well.